Relationships among emotional and material rewards, job satisfaction, burnout, affective commitment, job performance, and turnover intention in the hotel industry - Koo, Bonhak; Yu, Jongsik; Chua, Bee Lia; Lee, Sanghyeop; Han, Heesup (Taylor & Francis, 2020)
This study was designed to identify the intricate associations among emotional rewards (compliment, opportunity, empowerment, and recognition), material rewards (promotion, certificate, incentive, and special leave), job satisfaction, burnout, affective commitment, job performance, and turnover intention in the hotel sector. A field survey method with a quantitative approach was used. Our results from multiple regression analysis revealed that emotional and material rewards and their dimensions are of importance in the formation of affective commitment, job performance, and turnover intention. In addition, findings from the series of mediation analysis revealed that job satisfaction and burnout played a complete/partial mediating role within the proposed theoretical framework. Overall, this research can help hotel researchers better understand the role of rewards and help practitioners develop an efficient reward system for hotel employees.